2023
DOI: 10.1186/s12985-023-02010-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-human immunodeficiency virus-1 activity of MoMo30 protein isolated from the traditional African medicinal plant Momordica balsamina

Abstract: Background Plants are used in traditional healing practices of many cultures worldwide. Momordica balsamina is a plant commonly used by traditional African healers as a part of a treatment for HIV/AIDS. It is typically given as a tea to patients with HIV/AIDS. Water-soluble extracts of this plant were found to contain anti-HIV activity. Methods We employed cell-based infectivity assays, surface plasmon resonance, and a molecular-cell model of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…The M. balsamina plant exhibits remarkable anti-HIV potential. In fact, the plant protein MoMo30 (30 kDa protein), isolated from M. balsamina, effectively inhibits HIV-1 in vitro at nanomolar levels while exhibiting minimal cellular toxicity at inhibitory concentrations [48]. This finding is in line with the work of Coleman et al (2022) [49].…”
Section: Biological Properties Of Momordica Balsaminasupporting
confidence: 68%
“…The M. balsamina plant exhibits remarkable anti-HIV potential. In fact, the plant protein MoMo30 (30 kDa protein), isolated from M. balsamina, effectively inhibits HIV-1 in vitro at nanomolar levels while exhibiting minimal cellular toxicity at inhibitory concentrations [48]. This finding is in line with the work of Coleman et al (2022) [49].…”
Section: Biological Properties Of Momordica Balsaminasupporting
confidence: 68%
“…The Momordica balsamina plant has demonstrated anti-HIV properties. Specifically, the plant protein MoMo30, isolated from Momordica balsamina, has been found to effectively inhibit HIV-1 at nanomolar levels while exhibiting minimal cellular toxicity at inhibitory levels [22], which agrees with the work of Coleman et al (2022) [23]. Khumalo et al (2023) demonstrated that oral administration of Momordica balsamina to prediabetic rats attenuated diabetes-associated renal function abnormalities by reducing damage and restoring renal function.…”
Section: Biological Properties Of Momordica Balsaminasupporting
confidence: 58%